Targeting the parietal memory network with tDCS in MCI: study protocol for a randomized controlled trial - Cankaya, Seyda; Akturk, Aynur; Karakus, Ayse; Hanoğlu, Lütfü; Mardinoglu, Adil; Yulug, Burak (Frontiers in Human Neuroscience, 2025)
BackgroundMild cognitive impairment (MCI) is a critical transitional stage in dementia related disorders. In that context, dorsolateral prefrontal cortex (DLPFC), and lateral parietal cortex (LPC) are subjected to neuropathological changes in MCI. Furthermore, alterations in parietal memory network (PMN) integrity and default mode network (DMN) also occur in MCI. Transcranial direct current stimulation (tDCS) is a promising neuroprotective tool that might interfere with cognitive decline in Alzheimer’s disease-MCI (aMCI) and Parkinson’s disease-MCI (PD-MCI) when applied to DLPFC or LPC separately.MethodsThis is a randomized and controlled study evaluating the effectiveness of tDCS in 120 patients (60 aMCI and 60 PD-MCI). Firstly, all patients will be randomly (1:1) divided into two groups: DLPFC (30 aMCI; 30 PD-MCI) and LPC (30 aMCI, 30 PD-MCI) for tDCS stimulation. Secondly, they will classify randomly (2:1) real and sham groups for tDCS applied to once a day for 10 days over 2 weeks. The stimulation will be delivered with a 2-mA current frequency and will last 20 min. The primary outcome assessment for this study will be the change in score from baseline to the end of (14-days and 90 days follow-up) the tDCS application for the neurocognitive tests. Potential outcome parameters will be discussed in the light of current literature to contribute to the new area of personalized non-invasive brain stimulation research in neurodegenerative diseases at early stages. The results of this study are expected to shed light on the neural underpinnings and pro-cognitive outcomes of tDCS. Potential outcome parameters will be discussed in the light of current literature to contribute to the new area of personalized non-invasive brain stimulation research in neurodegenerative diseases at early stages.